Design and Synthesis of Some New Quinoline Based 1,2,3-Triazoles as Antimicrobial and Antimalarial Agents - Y., Parthasaradhi; S., Suresh; B., Ranjith Kumar; T., Savitha Jyostna (Orbital: The Electronic Journal of Chemistry, 2015)
A series of novel 6-bromo-2-chloro-3-(4-phenyl-[1,2,3]triazol-1-ylmethyl)-quinoline and its derivatives (5a-j) were synthesized in good yields from the intermediates (6-bromo-2-chloro-quinolin-3-yl)-methanol (2), methanesulfonic acid (6-bromo-2-chloroquinolin-3-yl)methyl methanesulfonate (3) and 3-azidomethyl-6-bromo-2-chloro-quinoline (4). The synthetic route leading to the title compounds is commenced from commercially available 6-bromo-2-chloro-quinolin-3-carbaldehyde (1). The chemical structures of the newly synthesized compounds were elucidated by their IR, 1H and 13C NMR, mass spectral data and elemental analysis. Further, all the target compounds were screened for their antimicrobial activity against various microorganisms and antimalarial activity towards P. falciparum.DOI: http://dx.doi.org/10.17807/orbital.v7i3.692